Fulminant hepatitis with microvesicular steatosis (a histologic comparison of cases occurring in Brazil - Labrea hepatitis - and in central Africa - Bangui hepatitis) - Andrade,Zilton A. (1992)
A similar histopathologic picture of fatal hepatitis associated with widespread acute fatty changes in hepatocytes and single-cell necrosis was seen in epidemic cases occurring in two distinct equatorial areas having high prevalences of HBV and HDV infections. The cases were previously considered to be two different entities; Labrea hepatitis in Brazil, and Bangui hepatitis in the Central African Republic. However, the histopathologic findings suggest that they are pathogenetically and etiologically related to HBVand HDV infections, probably modified by some as yet unknown factor (s) present in equatorial forest zones.